Analysis of The Motive of Neglect and Failed Family Communication that Build the Main Conflict in Novel “Everything I Never Told You” By Celeste Ng - Nadiyah, Khalda (Linguistika Kultura, 2025)
This research aims to determine the motives for neglect and failure of family communication that trigger the main conflict in the novel “Everything I Never Told You” written by Celeste Ng by analyzing the characterization of each character in the novel. In order to achieve this, this research employs a new criticism approach. The descriptive qualitative method was chosen as the research method in this study to characterize and interpret data. The primary data source, the novel “Everything I Never Told You”, is where the writer gathered the dialogues, words, and sentences. Additional supporting data from journals and articles are also used to strengthen the data. The main problem of this research can be seen from the development of plot, each characters’ characterization, and some symbolisms that appear in the novel. The plot is formed by going back and forth, showing how problems form and occur in the novel. The characterization of each character shows why an action is taken, and explains why the main conflict can occur between the characters. The symbolism that the author expresses several times strengthens the main problem found.